PENGADAAN BAHAN AJAR DIGITAL BERORIENTASI TELEPON GENGGAM DENGAN MEMANFAATKAN TXT CONVERTER - Baiq Muli Harisanti; Lalu Habiburrahman (Bioscientist : Jurnal Ilmiah Biologi, 2015)
The research entitled "Procurement of Handheld Oriented Digital Teaching Materials by Utilizing TXT Converter", this was motivated by the findings of previous research entitled "Learning to Write Scientific Oriented Work on Mobile Phones by Utilizing MJ Bookmaker 4.7.0.258". The findings are as follows: first, the development of jar file type teaching materials to present teaching materials on student mobile phones using the MJ Bookmaker, it can only be applied to certain mobile phones that support java MIDP 2.0 and 2.1. These devices are generally the types of mobile phones produced by trademarks that have been victorious such as Nokia (Simbian), Sony Ericson, and others. The second finding of the study, from the survey of the distribution of mobile phone users involving the number of respondents as many as 142 people from different classes, found the following data: the number of mobile phone users who support Java MIDP 2.0 and 2.1 are 44 people; mobile phone users with Blackberry operating systems as many as 15 users; Users of mobile phones with operating systems (suspected) of Android, 35 users; Windows Phone and Apple users each have 1 user; Users of mobile phones without an operating system are 15 users; 13 people did not have cellphones and 18 respondents without information. This research will be classified into an exploratory design, the instrument development model with an emphasis on quantitative design (quantitative development emphasized). The results of the study are as follows: a. The development of mobile phone-oriented teaching materials by utilizing TXT Converter is the development of minimal cost, even free teaching materials. This condition allows each subject to have teaching materials that will not burden students in terms of costs; b. The TXT data format allows background data images and colors such as PDF and MS. Word is deleted automatically, this will later accelerate the process of accessing data, especially on mobile phones with small memory: c. By presenting learning on mobile phones, teaching materials will later be mobile following wherever, wherever, whenever and under any circumstances the student. From this condition, students are expected to be able to access teaching materials without limits.